Customer Loyalty With Customer Satisfaction As A Mediating Variable At Toko Damai In Kendari - Chris Michael Tendian (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to analyze the effect of service quality, price and location on customer loyalty with customer satisfaction as a mediating variable. This study uses a quantitative approach that is carried out at a supermarket retail store called Toko Damai which is located in Kendari City. Respondents from this study were customers who shopped at Toko Damai. The population and sample withdrawal method in this study is non-probability sampling using purposive sampling technique. This study provides results that indicate that service quality affects customer satisfaction by 0.247 (on a Likert scale of 1-5), while the price is 0.281 (on a Likert scale of 1-5) and the location that has the highest influence on the three variables is 0.370 (on a Likert scale of 1-5). This also indicates that each variable positively and significantly affects consumer satisfaction. In addition, consumer satisfaction has also been shown to have a positive and significant impact on consumer loyalty. The effect is recorded at 0.565 (on a Likert scale of 1-5) and is the same in the opposite direction.